Insulin resistance parameters in children born very preterm and adequate for gestational age - Hernán García; Carolina Loureiro; Helena Poggi; Ivonne D'Apremont; Rosario Moore; José Tomás Ossa; María José Bruera; Soledad Peredo; Jacqueline Carvajal; Claudia Trincado; Alejandro Martínez‐Aguayo (Endocrinology, Diabetes & Metabolism, 2022)
Abstract Background Preterm neonates are at risk for metabolic syndrome later in life. Whether prematurity constitutes an independent risk factor for the development of cardiovascular disease and metabolic syndrome remains controversial. Objective To compare anthropometric measures, cardiometabolic risk factors and insulin resistance variables between children who were born very preterm (VPT, <32 gestational weeks) and at term (Term, >37 gestational weeks) and adequate for gestational age (AGA). Methods We designed a cross‐sectional cohort study, recruiting 120 children (5.0–8.5 years old) from the preterm clinic at Red de Salud UC‐Christus and Complejo Asistencial Dr. Sótero del Río, and term children from the community. We excluded children born small for gestational age, based on INTERGROWTH21. Anthropometrics data were classified using WHO reference standards. The homeostasis model assessment insulin resistance (HOMA‐IR) index, quantitative insulin sensitivity check index (QUICKI), triglyceride‐to‐HDL‐C ratio (TG/HDL‐C) and Pediatric Score Index for Metabolic Syndrome (PsiMS) were calculated. Results VPT children born AGA had lower HDL cholesterol levels (p = .019) and a higher PsiMS score than those born at term (p = .043). We observed a higher percentage of children with HDL cholesterol ≤40 mg/dl (13.0% vs. 2.3%, p = .026) and BP ≥90th percentile among the VPT children than among the Term children (26.0% vs. 11.6%, p = .031). Conclusions At school age, blood pressure was higher, and HDL‐C was lower among VPT children born AGA, suggesting a potential metabolic risk; therefore, it is essential to follow this group throughout their lives.